TECHNOLOGIES OF TEACHING PHTHISIOLOGY AT THE URGENCH BRANCH OF THE TASHKENT MEDICAL ACADEMY AS A MEANS IMPROVING THE QUALITY OF EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Education of the younger generation is the main task of the Republic of Uzbekistan.The analysis of innovative educational technologies plays a crucial role in teaching medical academy students.Which are used in the modern educational process.The article presents the basic methodological principles of teaching phthisiology, tuberculosis problems, which can ensure the effectiveness of the use of innovative educational technologies. Also improve the quality of education.